The Uyghur Community Diaspora, Identity and Geopolitics (Politics and History in Central Asia, 2018)
This book analyses the Uyghur community, presenting a brief historical background of the Uyghurs and debating the challenges of emerging Uyghur nationalism in the early 20th century. It elaborates on key issues within the community, such as the identity and current state of religion and worship. It also offers a thoughtful and comprehensive analysis of the Uyghur diaspora, addressing the issue of identity politics, the position of the Uyghurs in Central Asia, and the relations of the Uyghurs with Beijing, notably analyzing the 2009 Urumqi clashes and their long term impact on Turkish-Chinese relations. Re-examining Urghur identity through the lens of history, religion and politics, this is a key read for all scholars interested in China, Eurasia and questions of ethnicity and religion.